2020
DOI: 10.1177/1715163520976161
|View full text |Cite
|
Sign up to set email alerts
|

Self-care education across Canadian pharmacy schools: Curriculum survey findings

Abstract: Background: Self-care instruction in pharmacy curricula is essential given the impact pharmacists have in caring for patients in the community and their evolving role in this area. The primary objective of this study was to strengthen our current understanding of self-care education across undergraduate Canadian pharmacy programs. Methods: A national curriculum survey and follow-up phone interview was conducted in 2019 to assess the quantity and quality of self-care instruction across Canadian pharmacy schools… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…In terms of implications, educators will be required to prepare students to prescribe both OTC medicines and POMs in their new role as an independent prescriber so it could be useful to use an integrated approach and heed the lessons learnt about barriers to effective OTC consultations from this current study and previous research [4,17,[31][32][33][34]. Moreover, experience from the UK and other countries such as, Australia, Canada, New Zealand and the United States of America about pharmacist prescribing [56,57] will be invaluable to inform future practice If a UK pharmacy graduate qualifies as an independent prescriber at the point of registration (licensing), it is possible that many who subsequently work in the community sector will manage similar clinical conditions as they are doing currently.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…In terms of implications, educators will be required to prepare students to prescribe both OTC medicines and POMs in their new role as an independent prescriber so it could be useful to use an integrated approach and heed the lessons learnt about barriers to effective OTC consultations from this current study and previous research [4,17,[31][32][33][34]. Moreover, experience from the UK and other countries such as, Australia, Canada, New Zealand and the United States of America about pharmacist prescribing [56,57] will be invaluable to inform future practice If a UK pharmacy graduate qualifies as an independent prescriber at the point of registration (licensing), it is possible that many who subsequently work in the community sector will manage similar clinical conditions as they are doing currently.…”
Section: Discussionmentioning
confidence: 93%
“…The challenge for educators will be to find a way to incorporate the new responsibilities in the degree program whilst retaining the value of other roles such as OTC consultations. It is already known from previous work that the teaching of self-care and OTC medicines to pharmacy students is inconsistent [31][32][33]. For example, when Nakhla and colleagues investigated self-care education in ten Canadian schools of pharmacy, they found that education provision varied extensively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Anecdotes from years past tell of the public turning to community pharmacists for help as the only healthcare provider in town, especially in rural parts of the country. 35 Pharmacists are highly regarded on this front. 36 , 37 Some attempts have been made to quantify this activity in Canada.…”
Section: Pharmacist Involvement In Minor Ailment Carementioning
confidence: 99%